2003
DOI: 10.1097/01.wcb.0000091765.61714.30
|View full text |Cite
|
Sign up to set email alerts
|

Activation Systems for Latent Matrix Metalloproteinase-2 are Upregulated Immediately after Focal Cerebral Ischemia

Abstract: During focal cerebral ischemia, matrix metalloproteinase-2 (MMP-2) can contribute to the loss of microvessel integrity within ischemic regions by degrading the basal lamina. MMP-2 is secreted in latent form (pro-MMP-2), but the activation of pro-MMP-2 in the ischemic territory has not been shown. Immunohistochemical and in situ hybridization studies of the expression of the direct activators of MMP-2, MT1-MMP and MT3-MMP, and the indirect activation system tissue plasminogen activator, urokinase (u-PA), its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 85 publications
3
110
0
1
Order By: Relevance
“…Earlier studies provided indirect evidence that MMP-2 played a key role in the initial opening of the BBB in rat brain (Rosenberg et al, 1998), and in the non-human primate brain (Heo et al, 1999;Chang et al, 2003). We combined in situ zymography, which identified the regions where the gelatinases, either MMP-2 or -9, were active, and gel zymography, which showed that the major form was MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies provided indirect evidence that MMP-2 played a key role in the initial opening of the BBB in rat brain (Rosenberg et al, 1998), and in the non-human primate brain (Heo et al, 1999;Chang et al, 2003). We combined in situ zymography, which identified the regions where the gelatinases, either MMP-2 or -9, were active, and gel zymography, which showed that the major form was MMP-2.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of this MMP-like activity and its source(s) have not been identified. However, pro-MMP-2, pro-MMP-9, MMP-14, MMP-16, and the activators of the latent MMPs (Chang et al, 2003), as well as MMP-3 (Rosenberg et al, 2001), are rapidly expressed in the ischemic regions after MCAO in several model systems.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Expression of MMP-9 and MMP-2 has been shown to be significantly increased during stroke in human 21 and animal models of focal ischemia. 19,20,22,23 MMP-9 is of particular interest in the context of acute brain ischemia, because selective upregulation of MMP-9 has been observed in the brains of patients with stroke. 24 Activation of MMP-9 with increased BBB permeability contributes to the early formation of vasogenic edema after focal cerebral ischemia.…”
Section: Introductionmentioning
confidence: 99%